Analysis Mineral Content in the Shell of Freshwater Mussel (Pilsbryoconcha exilis) in Varied Sizes - Rahayu, Rizki; Leksono, Tjipto; ', Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this study was to determine the mineral content in freshwater mussel shell crude extractin varied shell sizes. The shell was categorized into three sizes, namely: small shell with the length of 7-8 cm (S), medium between 9-11 cm (M) and large between 13-14 cm (L). The laboratory analysis includedthe yield of shell crude extract, moisture content and the content of macro and micro minerals. The results showed that the freshwater mussel shell with the length of 7-8cm (S) had the lowest yield of shell crude extract 44,12%, but contained the highest mineral content, namely: macro minerals: calcium (Ca) 31.25%, magnesium (Mg) 0.29%, potassium (K) 3.24%, sodium (Na) 3.62%, phosphorus (P) 0.33%, and micro minerals: iron (Fe) 2.54 % and zinc (Zn) 0.91%.Keywords: Mineral, flour freshwater mussels shells, shells size